The Fate of the Tumor in the Hands of Microenvironment: Role of TAMs and mTOR Pathway - Danilo Figueiredo Soave; Marina Pacheco Miguel; Fernanda Dias Tomé; Liliana Borges de Menezes; Patrícia Resende Alo Nagib; Mara Rúbia Nunes Celes (Hindawi Limited, 2016)
Since 2000, written with elegance and accuracy, Hanahan and Weinberg have proposed six major hallmarks of cancer and, together, they provide great advances to the understanding of tumoral biology. Our knowledge about tumor behavior has improved and the investigators have now recognized that inflammatory microenvironment may be a new feature for the tumor entities. Macrophages are considered as an important component of tumoral microenvironment. Biologically, two forms of activated macrophages can be observed: classically activated macrophages (M1) and alternative activated macrophages (M2). Despite the canonical pathways that control this puzzle of macrophages polarization, recently, mTOR signaling pathway has been implicated as an important piece in determining the metabolic and functional differentiation of M1 and M2 profiles. Currently, it is believed that macrophages related to tumoral microenvironment present an "M2-like" feature promoting an immunosuppressive microenvironment enhancing tumoral angiogenesis, growth, and metastasis. In the present review we discuss the role of macrophages in the tumor microenvironment and the role of mTOR pathway in M1 and M2 differentiation. We also discuss the recent findings in M1 and M2 polarization as a possible target in the cancer therapy.